К вопросу о польских сельских общинах Северного Кавказа в межвоенный период (1918–1939) - Акопян, Виктор (Acta Polono-Ruthenica, 2020)
This article examines the state of Polish communities in rural areas of the North Caucasus between the two world wars. The author notes that mono-ethnic settlements of Poles were not formed in the region for various reasons. This was the result of both objective reasons (dispersion of the Polish settlement, predominance of social groups and professions characteristic of urban life) and the result of the conscious policy of the tsarist (royal) and Soviet authorities (after the Civil War) which prevented their creation. Despite the small number of the Polish rural population, they had more customs, traditions, faith, language and national identity for a long time than their urban compatriots.